Polyolefin-based film and its manufacturing method, separator, secondary battery, and power consumption device
Patent Information
- Application Number
- JP2024552473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-04-18
- Publication Date
- 2025-03-13
AI Technical Summary
【0040】 上記説明は、本出願の技術案の概要に過ぎず、本出願の技術手段をより明瞭に理解するために、明細書の内容に従って実施することができ、そして本出願の上記及び他の目的、特徴と利点をより明瞭に且つ分かりやすくするために、以下は、特に本出願の具体的な実施形態を挙げて説明する。
Smart Images

Figure 2025507030000001 
Figure 2025507030000002 
Figure 2025507030000003
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims priority to international patent application No. PCT / CN2022 / 104965, filed on July 11, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to the field of battery technology, and in particular to a polyolefin-based film and its manufacturing method, a separator, a secondary battery, and a power consuming device. [Background technology]
[0003] With the development of technology, clean energy such as batteries will gradually replace traditional fossil energy and provide power for various scenes. In secondary batteries, separators are used to separate the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other and causing short circuits. As people's demand for the use of portable products increases day by day, ultra-thin separators have begun to be widely used. However, the polyolefin-based films used to manufacture conventional ultra-thin separators cannot achieve both thin thickness and excellent heat shrinkability.
[0004] Therefore, there is a strong demand for the development of a polyolefin-based film that can achieve both a thin thickness, high puncture strength, and excellent heat shrinkability. Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the problems existing in the background art, the present application provides a polyolefin-based film that can achieve both a thin thickness and excellent heat shrink performance. [Means for solving the problem]
[0006] The polyolefin base film according to the first embodiment of the present application comprises polyolefins having different weight average molecular weights, the thickness of the polyolefin base film being ≦6 μm, the longitudinal shrinkage rate of the polyolefin base film being ≦2% and the transverse shrinkage rate being ≦1% at 115° C. / 1 h.
[0007] In the technical proposal of the embodiment of the present application, polyolefins with different weight average molecular weights are combined as raw materials, and the resulting polyolefin base film has an ultra-thin thickness and low thermal shrinkage rate. The energy density of the battery core can be improved to a certain extent by reducing the thickness of the polyethylene base film.
[0008] Furthermore, the obtained polyolefin base film has a relatively high puncture strength, and the improvement of the puncture strength and the reduction of the thermal shrinkage rate can improve the pass rate of the bare cell short circuit test and improve the safety performance of the battery core.
[0009] In addition, reducing the thermal shrinkage rate contributes to improving the heat resistance of the polyolefin base film, and can delay the thermal failure of adjacent battery cores when a battery core experiences thermal runaway.
[0010] In some embodiments, according to the first aspect, a first example of the first aspect is provided, in which the thickness of the polyolefin base film is 0.5 to 6 μm, optionally the puncture strength of the polyolefin base film is ≧380 gf, more optionally the puncture strength of the polyolefin base film is 380 to 1000 gf, even more optionally the puncture strength of the polyolefin base film is 400 to 600 gf, and optionally the longitudinal shrinkage rate of the polyolefin base film at 115° C. / 1 h is 0% to 1.8%, and the transverse shrinkage rate is 0% to 0.8%.
[0011] In this design, the thickness, puncture strength and heat shrinkage rate of the polyolefin-based film are reasonably controlled to trade off the puncture strength and thermal stability of the polyolefin-based film, thereby meeting the comprehensive performance requirements in the practical application of ultra-thin separators.
[0012] In some embodiments, according to the first aspect, there is provided a second example of the first aspect, wherein the polyolefin comprises a first polyethylene and a second polyethylene, wherein the weight average molecular weight of the first polyethylene is ≧800,000, optionally the weight average molecular weight of the first polyethylene is 800,000 to 3,000,000, and the weight average molecular weight of the second polyethylene is ≦600,000, optionally the weight average molecular weight of the second polyethylene is 300,000 to 600,000.
[0013] In this design, a mixture of high molecular weight polyethylene and low molecular weight polyethylene is used, and the molecular weight range is optimized, so that the resulting ultra-thin polyolefin base film has both high puncture strength and low heat shrinkage.The ultra-thin polyolefin base film produced by using only low molecular weight polyethylene cannot meet the requirements in terms of mechanical strength, and the processing difficulty of using only high molecular weight polyethylene to produce an ultra-thin polyolefin base film is very large, it is difficult to tensile at a large ratio, it is not suitable for industrialized large-scale production, and the thickness consistency of the obtained base film is poor.
[0014] In some embodiments, according to the first aspect, there is provided a third example of the first aspect, wherein the mass ratio of the first polyethylene to the second polyethylene is 3:7 to 9.9:0.1.
[0015] In this design, by optimizing the mass occupancy ratio of the first polyethylene and the second polyethylene, the thickness of the polyolefin base film can be further reduced, the pin puncture strength can be improved, and the heat shrinkage rate can be reduced.
[0016] In some embodiments, according to the first aspect, there is provided a fourth example of the first aspect, wherein the polyolefin comprises one or two of polypropylene and polyethylene.
[0017] In some embodiments, according to the first aspect, a fifth example of the first aspect is provided, wherein the polyolefin base film has a longitudinal tensile strength of ≥ 3800 kgf / cm 2 The transverse tensile strength of polyolefin base film is ≧3000kgf / cm 2 It is.
[0018] This design increases the tensile strength of the polyolefin-based film, which is favorable for effective coating of metal particles and negative and positive electrode particles in bare cells, and prevents internal short circuits from occurring during the manufacturing process of the battery core.
[0019] In some embodiments, according to the first aspect, there is provided a sixth example of the first aspect, the polyolefin base film comprising: (1) The porosity of the polyolefin base film is 25 to 40%; (2) The polyolefin base film has an air permeability of 100 to 160 s / 100 cc; (3) The surface density of the polyolefin base film is 2.8 to 3.6 g / m 2 The present invention has one or more of the following characteristics:
[0020] In this design, efficient ion conduction can be achieved by optimizing the pore size structure of the polyethylene-based film.
[0021] In some embodiments, according to the first aspect, there is provided a seventh example of the first aspect, wherein the crystallinity of the polyolefin base film is ≧75%, and optionally the crystallinity of the polyolefin base film is 75-85%.
[0022] A second aspect of the present application provides a method for producing a polyolefin-based film, the method comprising: A method for producing a film sheet from a mixture of polyolefins having different weight average molecular weights and a pore-forming agent, the mixture having a total weight of the polyolefins being 15 to 35 wt % of the mixture; A biaxial tension is applied to the film sheet, and the longitudinal tension ratio is 5 to 50 times and the transverse tension ratio is 5 to 50 times, and optionally the longitudinal tension ratio is 5 to 20 times and the transverse tension ratio is 5 to 20 times; removing the pore-forming agent to form voids; and tensile fixing and heat fixing the film sheet to obtain a polyolefin base film.
[0023] In the technical solutions of the embodiments of the present application, polyolefins with different weight average molecular weights can be used to produce ultra-thin polyolefin-based films with a large cross-draw / longitudinal draw ratio and low heat shrinkage.
[0024] Furthermore, the higher the puncture strength of the polyolefin base film, the higher its puncture resistance against metal particles, which can effectively avoid short circuits in the bare cell caused by negative electrode particles, positive electrode particles, and metal foreign objects piercing the separator at a certain pressure. Therefore, improving the puncture strength of the polyolefin base film can improve the pass rate of the bare cell short circuit test.
[0025] Also, increasing the tensile ratio can increase the orientation between polyolefin molecules, improving the crystallinity of the ultra-thin polyethylene base film, thereby improving its thermal stability.
[0026] In some embodiments, according to the second aspect, a first example of the second aspect is provided, in which the occupancy rate of the polyolefin in the mixture is 20 to 30 wt% of the total weight, the longitudinal tensile magnification is 10 to 20 times, and the transverse tensile magnification is 10 to 20 times.
[0027] In this design, by optimizing the polyolefin occupancy rate, longitudinal tensile ratio and transverse tensile ratio, the thickness of the polyolefin base film can be further reduced, the pin puncture strength can be improved, and the heat shrinkage rate can be reduced.
[0028] In some embodiments, according to the second aspect, there is provided a second example of the second aspect, where the biaxial tensioning causes the polyolefin base film to have a crystallinity of ≧75%, and optionally, the biaxial tensioning causes the polyolefin base film to have a crystallinity of 75-85%.
[0029] In some embodiments, according to the second aspect, there is provided a third example of the second aspect, wherein the polyolefin comprises a first polyethylene and a second polyethylene, wherein: The weight average molecular weight of the first polyethylene is ≧800,000, and optionally the weight average molecular weight of the first polyethylene is 800,000 to 3,000,000; The weight average molecular weight of the second polyethylene is ≦600,000, and optionally the weight average molecular weight of the second polyethylene is 300,000 to 600,000.
[0030] In this design, a mixture of high molecular weight polyethylene and low molecular weight polyethylene is used, and the molecular weight range is optimized, so that the resulting ultra-thin polyolefin base film has both high puncture strength and low heat shrinkage.The ultra-thin polyolefin base film produced by using only low molecular weight polyethylene cannot meet the requirements in terms of mechanical strength, and the processing difficulty of using only high molecular weight polyethylene to produce an ultra-thin polyolefin base film is very large, it is difficult to tensile at a large ratio, it is not suitable for industrialized large-scale production, and the thickness consistency of the obtained base film is poor.
[0031] In some embodiments, according to the second aspect, there is provided a fourth example of the second aspect, wherein the mass ratio of the first polyethylene to the second polyethylene is 3:7 to 9.9:0.1.
[0032] In this design, by optimizing the mass occupancy ratio of the first polyethylene and the second polyethylene, the thickness of the polyolefin base film can be further reduced, the pin puncture strength can be improved, and the heat shrinkage rate can be reduced.
[0033] In some embodiments, according to the second aspect, there is provided a fifth example of the second aspect, wherein the pore-forming agent comprises one or more of white oil, liquid paraffin, mineral oil, soybean oil, phthalate ester, and aromatic ether.
[0034] A third aspect of the present application provides a separator comprising the polyolefin base film according to the first aspect of the present application or the polyolefin base film obtained by the production method according to the second aspect of the present application.
[0035] In the technical solutions of the embodiments of the present application, the polyolefin-based film of the first aspect of the present application or the polyolefin-based film obtained by the manufacturing method of the second aspect of the present application is used, so that the separator of the present application has advantages such as ultra-thinness, high puncture strength, and low thermal shrinkage rate.
[0036] A fourth aspect of the present application provides a secondary battery including the separator according to the third aspect of the present application.
[0037] In the technical solutions of the embodiments of the present application, the polyolefin-based film of the first aspect of the present application or the polyolefin-based film obtained by the manufacturing method of the second aspect of the present application is used, so that the secondary battery of the present application has advantages such as ultra-thinness, high puncture strength, and low thermal shrinkage rate.
[0038] A fifth aspect of the present application provides a power consuming device including the secondary battery according to the fourth aspect of the present application.
[0039] In the technical solutions of the embodiments of the present application, the polyolefin-based film of the first aspect of the present application or the polyolefin-based film obtained by the manufacturing method of the second aspect of the present application is used, so that the power consumption device of the present application has advantages such as ultra-thinness, high puncture strength and low thermal shrinkage rate.
[0040] The above description is only an outline of the technical solution of the present application, which can be implemented in accordance with the contents of the specification, in order to make the technical means of the present application more clearly understood; and in order to make the above and other objectives, features and advantages of the present application more clear and understandable, the following particularly cites specific embodiments of the present application to describe them. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0041] Hereinafter, exemplary embodiments of the present disclosure will be described in more detail. Although exemplary embodiments of the present disclosure are shown, it should be understood that the present disclosure is not limited to the embodiments described herein, but may be realized in various forms. Rather, these embodiments are provided to allow the present disclosure to be more fully understood, and to fully convey the scope of the present disclosure to those skilled in the art.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art of the present application, and the terms used herein are only for describing specific examples and are not intended to limit the present application. The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover a non-exclusive inclusion.
[0043] For convenience, only some numerical ranges are explicitly disclosed herein. However, any lower limit and any upper limit can be combined to form a range not expressly described, and any lower limit and another lower limit can be combined to form a range not expressly described, and similarly any upper limit and any other upper limit can be combined to form a range not expressly described. It should be noted that, although not expressly described, each point or single value between the range endpoints is included in this range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit, or with another lower limit or upper limit to form a range not expressly described.
[0044] In the description of this specification, it should be explained that unless otherwise specified, "more than" and "less than" are inclusive, and "multiple" in "one or more" means two or more (including two).
[0045] With the development of technology, clean energy such as batteries will gradually replace traditional fossil energy and provide power for various scenes. In secondary batteries, separators are used to separate the positive and negative electrodes and prevent the positive and negative electrodes from directly contacting each other and causing short circuits. As people's demand for the use of portable products increases day by day, ultra-thin separators have begun to be widely used. However, the polyolefin-based film used to manufacture conventional ultra-thin separators cannot achieve a thin thickness, high puncture strength, and excellent heat shrinkage performance at the same time. Therefore, there is a strong demand for the development of a polyolefin-based film that can achieve a thin thickness, high puncture strength, and excellent heat shrinkage performance at the same time.
[0046] Researchers found that the thinner the polyolefin-based film, the worse its mechanical performance, such as the lower the puncture strength, and the higher the thermal shrinkage, which poses the risk of direct contact between the positive and negative electrodes and causing a short circuit during use as a separator.
[0047] In order to solve this technical problem, the inventors have studied and designed a polyolefin-based film by combining polyolefins with different weight-average molecular weights as raw materials, and the resulting polyolefin-based film has an ultra-thin thickness and at the same time has high puncture strength and low thermal shrinkage. By reducing the thickness of the polyethylene-based film, the energy density of the battery core can be improved to a certain extent. The improvement of the puncture strength and the reduction of the thermal shrinkage can improve the pass rate of the bare cell short circuit test and improve the safety performance of the battery core. In addition, the reduction of the thermal shrinkage can contribute to the improvement of the heat resistance of the polyolefin-based film, and can delay the thermal failure of the adjacent battery core when the battery core goes into thermal runaway.
[0048] The technical solutions described in the embodiments of the present application are applicable to polyolefin-based films, and also to a manufacturing process for the polyolefin-based films, a separator using the polyolefin-based films, a secondary battery using the separator, a battery module using the secondary battery, a battery pack using the battery module, and a power consumption device using at least one of the secondary battery, the battery module, and the battery pack.
[0049] According to a first aspect, in some embodiments of the present application, the present application provides a polyolefin base film. The polyolefin base film may include polyolefins having different weight average molecular weights. The polyolefin base film has a thickness of ≦6 μm, a machine direction (MD) shrinkage rate of ≦2%, and a transverse direction (TD) shrinkage rate of ≦1%.
[0050] In the technical proposal of the embodiment of the present application, polyolefins with different weight average molecular weights are combined and used as raw materials. High molecular weight polyolefins have relatively long polyolefin molecular chains, which improve the entanglement of the molecular chains and increase the strength of the base film. The addition of low molecular weight polyolefins can improve the manufacturability of polyolefins. The resulting polyolefin base film has an ultra-thin thickness and high puncture strength at the same time. The tensile ratio can be increased to cause secondary crystallization of the polyolefin molecular chains, improve the high temperature resistance of the separator, and reduce the thermal shrinkage rate of the separator.
[0051] In some embodiments, according to the first aspect, there is provided a first example of the first aspect, wherein the polyolefin base film has a thickness of 0.5-6 μm.
[0052] Furthermore, the puncture strength of the polyolefin base film is ≧380 gf, and more preferably, the puncture strength of the polyolefin base film may be 380 to 1000 gf, and further preferably, the puncture strength may be 400 to 600 gf.
[0053] Furthermore, the polyolefin base film may have a longitudinal shrinkage rate of 0% to 1.8% at 115° C. / 1 h, and a transverse shrinkage rate of 0% to 0.8%.
[0054] In this design, the thickness, puncture strength and heat shrinkage rate of the polyolefin-based film are reasonably controlled to trade off the puncture strength and thermal stability of the polyolefin-based film, thereby meeting the comprehensive performance requirements in the practical application of ultra-thin separators.
[0055] In some specific embodiments, the thickness of the polyolefin base film may be, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, or 6 μm. Optionally, the thickness of the polyolefin base film may be 2-6 μm, 3-6 μm, 4-6 μm, or 5-6 μm.
[0056] In some specific embodiments, the puncture strength of the polyolefin base film may be, for example, 380gf, 390gf, 400gf, 410gf, 420gf, 430gf, 440gf, 450gf, 460gf, 470gf, 480gf, 490gf, 500gf, 510gf, 520gf, 530gf, 540gf, 550gf, 560gf, 570gf, 580gf, 590gf, 600gf, 700gf, 800gf, 900gf, or 1000gf. Optionally, the puncture strength of the polyolefin base film may be 400-550gf, 400-500gf, or 400-450gf.
[0057] In some specific embodiments, the longitudinal shrinkage of the polyolefin base film at 115° C. / 1 h may be, for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7% or 1.8%. Alternatively, the longitudinal shrinkage of the polyolefin base film at 115° C. / 1 h may be 0.5% to 1.8%, 1.0% to 1.8%, or 1.3% to 1.8%.
[0058] In some specific embodiments, the transverse shrinkage of the polyolefin base film at 115° C. / 1 h may be, for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%. Optionally, the transverse shrinkage of the polyolefin base film at 115° C. / 1 h may be 0.3% to 0.8%.
[0059] In some embodiments, according to the first aspect, there is provided a second example of the first aspect, wherein the polyolefin comprises a first polyethylene and a second polyethylene. The first polyethylene has a weight average molecular weight of ≥ 8.0 x 10 5 The weight average molecular weight of the second polyethylene is ≦6.0×10 5 It is.
[0060] In this design, a mixture of high molecular weight polyethylene and low molecular weight polyethylene is used, and the molecular weight range is optimized, so that the resulting ultra-thin polyolefin base film has both high puncture strength and low heat shrinkage.The ultra-thin polyolefin base film produced by using only low molecular weight polyethylene cannot meet the requirements in terms of mechanical strength, and the processing difficulty of using only high molecular weight polyethylene to produce an ultra-thin polyolefin base film is very large, it is difficult to tensile at a large ratio, it is not suitable for industrialized large-scale production, and the thickness consistency of the base film is poor.
[0061] In some specific embodiments, the weight average molecular weight of the first polyethylene is 8.0×10 5 ~30.0×10 5 For example, 8.0×10 5 , 9.0×10 5 , 10.0×10 5 , 11.0×10 5 , 12.0×10 5 , 13.0×10 5 , 14.0×10 5 , 15.0×10 5 , 16.0×10 5 , 17.0×10 5 , 18.0×10 5 , 19.0×10 5 , 20.0×10 5 , 25.0×10 5 , 30.0×10 5 Optionally, the weight average molecular weight of the first polyethylene may be 8.0×10 5 ~30.0×10 5 , 8.0×105 ~15.0×10 5 Or 8.0 x 10 5 ~10.0×10 5 may be also possible.
[0062] In some specific embodiments, the weight average molecular weight of the second polyethylene is 1.0×10 5 ~6.0×10 5 For example, 1.0×10 5 , 2.0×10 5 , 3.0×10 5 , 4.0×10 5 , 5.0×10 5 Or 6.0 x 10 5 Optionally, the weight average molecular weight of the second polyethylene may be 1.0×10 5 ~3.0×10 5 , 2.0×10 5 ~4.0×10 5 Or 3.0 x 10 5 ~5.0×10 5 Or 3.0 x 10 5 ~6.0×10 5 may be also possible.
[0063] In some embodiments, according to the first aspect, there is provided a third example of the first aspect, wherein the mass ratio of the first polyethylene to the second polyethylene may be from 3:7 to 9.9:0.1.
[0064] In this design, by optimizing the mass occupancy ratio of the first polyethylene and the second polyethylene, the thickness of the polyolefin base film can be further reduced, the pin puncture strength can be improved, and the heat shrinkage rate can be reduced.
[0065] In some specific embodiments, the mass ratio of the first polyethylene to the second polyethylene may be, for example, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, or 9.9:0.1. Optionally, the mass ratio of the first polyethylene to the second polyethylene may be from 3:7 to 5:5 or from 4:6 to 6:4.
[0066] In some embodiments, according to the first aspect, a fourth example of the first aspect is provided, wherein the polyolefin base film has a longitudinal tensile strength of ≥ 3800 kgf / cm 2 The transverse tensile strength of polyolefin base film is ≧3000kgf / cm 2 It is.
[0067] This design increases the tensile strength of the polyolefin-based film, which is favorable for effective coating of metal particles and negative and positive electrode particles in bare cells, and prevents internal short circuits from occurring during the manufacturing process of the battery core.
[0068] In some specific embodiments, the polyolefin base film has a longitudinal tensile strength of 4000 to 6000 kgf / cm 2 Alternatively, 4000 to 5000 kgf / cm 2 , for example 4000kgf / cm 2 , 4100kgf / cm 2 , 4200kgf / cm 2 , 4300kgf / cm 2 , 4400kgf / cm 2 , 4500kgf / cm 2 , 4600kgf / cm 2 , 4700kgf / cm 2 , 4800kgf / cm 2 , 4900kgf / cm 2 or 5000kgf / cm 2 may be also possible.
[0069] In some specific embodiments, the transverse tensile strength of the polyolefin base film is 3200 to 5000 kgf / cm 2 Alternatively, 3200 to 4000 kgf / cm 2 , for example 3200kgf / cm 2 , 3300kgf / cm 2 , 3400kgf / cm 2 , 3500kgf / cm 2 , 3600kgf / cm 2 , 3700kgf / cm 2, 3800kgf / cm 2 , 3900kgf / cm 2 or 4000kgf / cm 2 may be also possible.
[0070] In some embodiments, according to the first aspect, providing a fifth example of the first aspect, the porosity of the polyolefin base film may be 25-40%.
[0071] In some embodiments, according to the first aspect, there is provided a sixth example of the first aspect, wherein the air permeability of the polyolefin base film may be 100 to 160 s / 100 cc.
[0072] In some embodiments, according to the first aspect, there is provided a seventh example of the first aspect, wherein the areal density of the polyolefin base film is 2.8 to 3.6 g / m 2 may be also possible.
[0073] In this design, efficient ion conduction can be achieved by optimizing the pore size structure of the polyethylene-based film.
[0074] In some specific embodiments, the porosity of the polyolefin base film may be, for example, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, or 40%. Optionally, the porosity of the polyolefin base film may be between 29% and 35%.
[0075] In some specific embodiments, the air permeability of the polyolefin base film may be, for example, 100s / 100cc, 110s / 100cc, 120s / 100cc, 130s / 100cc, 140s / 100cc, 150s / 100cc, or 160s / 100cc. Optionally, the air permeability of the polyolefin base film may be 140-160s / 100cc.
[0076] In some specific examples, the areal density of the polyolefin base film is, for example, 2.8 g / m 2 , 2.9g / m 2 , 3.0g / m 2 , 3.1g / m 2 , 3.2g / m 2 , 3.3g / m 2 , 3.4g / m 2 , 3.5g / m 2 or 3.6 g / m 2 Optionally, the areal density of the polyolefin base film may be 3.3 to 3.6 g / m 2 may be also possible.
[0077] In some specific embodiments, the polyolefin base film has a crystallinity of ≧75%, such as 75%, 77%, 78%, 79%, 80%, 82%, 85%, 90%, or 95%. Optionally, the polyolefin base film has a crystallinity of 75-85%.
[0078] In some specific examples, the conductivity of the polyethylene-based films of the present application may be 0.6 ms / cm or greater.
[0079] In some embodiments, according to the first aspect, there is provided an eighth example of the first aspect, where the stretch ratio in the longitudinal direction of the polyolefin base film may be 40% to 120%, and the stretch ratio in the transverse direction may be 80% to 120%.
[0080] In some specific embodiments, the stretch ratio of the polyolefin base film in the longitudinal direction may be, for example, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 110% or 120%. Optionally, the stretch ratio of the polyolefin base film in the longitudinal direction is 50% to 110% or 55% to 105%.
[0081] In some specific embodiments, the stretch ratio of the polyolefin base film in the transverse direction may be, for example, 80%, 90%, 100%, 110% or 120%. Optionally, the stretch ratio of the polyolefin base film in the transverse direction is 90% to 110%.
[0082] The polyolefin may include, but is not limited to, one or two of polypropylene and polyethylene.
[0083] A second aspect of the present application provides a method for producing a polyolefin-based film, the method comprising: A method for producing a film sheet from a mixture of polyolefins having different weight average molecular weights and a pore-forming agent, the mixture having a total weight of the polyolefins being 15 to 35 wt % of the mixture; The film sheet is biaxially stretched, and the longitudinal stretching ratio is 5 to 50 times and the transverse stretching ratio is 5 to 50 times; removing the pore-forming agent to form voids; and tensile fixing and heat fixing the film sheet to obtain a polyolefin base film.
[0084] In the technical proposal of the embodiment of the present application, polyolefins with different weight average molecular weights can be used to produce an ultra-thin polyolefin base film with a suitable cross-draw / longitudinal draw ratio, high puncture strength, and low heat shrinkage. The higher the puncture strength of the polyolefin base film, the higher its puncture resistance against metal particles, and the negative electrode particles, positive electrode particles, and metal foreign objects can effectively avoid short circuits in bare cells caused by piercing the separator with a certain pressure, so that improving the puncture strength of the polyolefin base film can improve the pass rate of the bare cell short circuit test. In addition, improving the tensile ratio can increase the orientation between polyolefin molecules, improving the crystallinity of the ultra-thin polyethylene base film, and thereby improving its thermal stability. The heat shrinkage performance of the ultra-thin polyethylene base film of the present application is superior to that of ordinary 7 μm or 9 μm thick polyethylene base films. This ultra-thin polyolefin base film can be used as a battery separator, which can not only improve the portability of the battery, but also improve the safety performance of the battery.
[0085] Furthermore, in the technical solution of this embodiment, the polyolefin-based film produced has the same characteristics and advantages as the polyolefin-based film described above, and will not be further described here.
[0086] In some embodiments, according to the second aspect, a first example of the second aspect is provided, and the occupancy rate of the polyolefin in the mixture of the total weight may be 20 to 30 wt %. The longitudinal tensile magnification may be 10 to 20 times, and the transverse tensile magnification may be 10 to 20 times. Furthermore, the longitudinal tensile temperature may be 108 to 114°C, and the transverse tensile temperature may be 113 to 118°C.
[0087] In this design, the polyolefin occupancy rate, longitudinal tensile ratio and transverse tensile ratio are optimized to further reduce the thickness of the polyolefin base film, improve the pin puncture strength and reduce the heat shrinkage rate.
[0088] In some specific embodiments, the occupancy rate of the polyolefins in the mixture may be, for example, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, or 30 wt%. Alternatively, the occupancy rate of the polyolefins in the mixture may be 20-25 wt%, 23-27 wt%, or 25-30 wt%.
[0089] In some specific embodiments, the longitudinal tensile ratio may be, for example, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, 16 times, 17 times, 18 times, 19 times, 20 times, 25 times, 30 times, 35 times, 40 times, 45 times, or 50 times. Optionally, the longitudinal tensile ratio may be 5 to 20 times, 10 to 15 times, 15 to 20 times, etc.
[0090] In some specific embodiments, the lateral tensile ratio may be, for example, 5x, 6x, 7x, 8x, 9x, 10x, 11x, 12x, 13x, 14x, 15x, 16x, 17x, 18x, 19x, 20x, 25x, 30x, 35x, 40x, 45x, or 50x. Optionally, the lateral tensile ratio is 5-20x, 10-15x, 15-20x, etc.
[0091] In some embodiments, according to the second aspect, there is provided a second example of the second aspect, where the biaxial tensioning causes the polyolefin base film to have a crystallinity of ≧75%, and optionally, the biaxial tensioning causes the polyolefin base film to have a crystallinity of 75-85%.
[0092] As can be appreciated, the polyolefin solutions and advantages are the same as in the first embodiment and will not be further described here.
[0093] The present application is not particularly limited to the pore-forming agent used, and any agent capable of sufficiently dissolving polyolefins may be used. For example, the pore-forming agent may be one or more of white oil, liquid paraffin, mineral oil, soybean oil, phthalic acid esters, and aromatic ethers, but is not limited thereto. Optionally, the pore-forming agent is white oil. In some specific embodiments, the pore-forming agent is white oil, and multiple polyolefins having different weight average molecular weights are mixed with the white oil to obtain a liquid mixture. In the liquid mixture, the occupancy rate of the polyolefin in the liquid mixture is the solid content of the polyolefin.
[0094] In some embodiments, according to the second aspect, providing a third example of the second aspect, the thickness of the film sheet may be 1 mm or more, optionally 1 to 5 mm, for example 1 mm, 2 mm, 3 mm, 4 mm, or 5 mm.
[0095] In some embodiments, according to the second aspect, there is provided a fourth example of the second aspect, where the biaxial tensioning includes performing longitudinal tension first and then transverse tension, or performing transverse tension first and then longitudinal tension, or performing longitudinal tension and transverse tension synchronously.
[0096] In some embodiments, according to the second aspect, a fifth example of the second aspect is provided, in which removing the pore-forming agent comprises extracting the pore-forming agent in the film sheet using an extractant. The type of the extractant can be selected according to the type of the pore-forming agent, and is mainly used to dissolve the pore-forming agent to form voids in the material. Optionally, the extractant is dichloromethane.
[0097] In some embodiments, according to the second aspect, there is provided a sixth example of the second aspect, in which the tension fixing includes tensioning the film sheet in the transverse direction at a small ratio. The tension ratio may be 1 to 3 times. The tension temperature may be 125 to 140°C.
[0098] In some embodiments, according to the second aspect, there is provided a seventh example of the second aspect, wherein the heat fixing comprises heating the film sheet to fix it. The heating temperature is ≧130° C., optionally 130-140° C., for example 132-136° C. The heating time is ≧20 s, optionally 20-60 s, for example 20-30 s.
[0099] A third aspect of the present application provides a separator comprising the polyolefin base film according to the first aspect of the present application or the polyolefin base film obtained by the production method according to the second aspect of the present application.
[0100] In the technical solutions of the embodiments of the present application, the polyolefin-based film of the first aspect of the present application or the polyolefin-based film obtained by the manufacturing method of the second aspect of the present application is used, so that the separator of the present application has advantages such as ultra-thinness, high puncture strength, and low thermal shrinkage rate.
[0101] In some embodiments, according to the third aspect, there is provided one example of the third aspect, wherein the separator further comprises a coating disposed on at least one surface of the polyolefin base film.
[0102] In some illustrative examples, the coating may include an organic coating, an inorganic coating, or a combination thereof.
[0103] Optionally, the organic coating comprises at least one of a polyvinylidene fluoride coating, a polystyrene coating, an aramid coating, a polyester coating, a polyarylate coating, a polyacrylonitrile coating, an aromatic polyamide coating, a polyimide coating, a polyethersulfone coating, a polyetherketone coating, and a polyetherimide coating.
[0104] Optionally, the inorganic coating may include a ceramic coating.
[0105] A fourth aspect of the present application provides a secondary battery including the separator according to the third aspect of the present application.
[0106] In the technical solutions of the embodiments of the present application, the polyolefin-based film of the first aspect of the present application or the polyolefin-based film obtained by the manufacturing method of the second aspect of the present application is used, so that the secondary battery of the present application has advantages such as ultra-thinness, high puncture strength, and low thermal shrinkage rate.
[0107] A fifth aspect of the present application provides a power consuming device including the secondary battery according to the fourth aspect of the present application.
[0108] The present invention will now be further described in conjunction with examples. It should be understood that these examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.
[0109] Manufacture of polyethylene-based films Example 1 First, the weight average (Mw) molecular weight is 8.0×10 5 The first polyethylene has a molecular weight of 3.0×10 5 The second polyethylene is selected and mixed in a mass ratio of 5:5, and then blended with white oil, where the solid content of polyethylene is 25%, and then heated and melted in an extruder, followed by cooling and casting, and then cooled and molded to obtain a 2mm cast film sheet, and the cast film sheet is stretched in the longitudinal and transverse directions, with a longitudinal tensile ratio of 11.2 times, a longitudinal tensile temperature of 110°C, a transverse tensile ratio of 10.7 times, and a transverse tensile temperature of 115°C. After keeping warm, a film sheet with an area increased by 120 times is obtained, and the white oil in the film sheet is extracted using dichloromethane to form voids, and the dried microporous film is stretched again in the transverse direction at a small ratio of 2 times, and the transverse tensile temperature is 133°C, and heat-fixed at 133°C to obtain a porous polyethylene base film with a thickness of 5.2 μm and a crystallinity of 79.1%.
[0110] Example 2 First, the molecular weight Mw is 8.0×10 5 The first polyethylene has a molecular weight of 3.0×10 5 The second polyethylene is selected and mixed in a mass ratio of 4:6, and then blended with white oil, where the solid content of polyethylene is 25%, and then heated and melted in an extruder, followed by cooling and casting, and cooling and forming to obtain a 2.1 mm cast film sheet, and the cast film sheet is stretched in the longitudinal and transverse directions, with a longitudinal tensile ratio of 10.3 times, a longitudinal tensile temperature of 110°C, a transverse tensile ratio of 10.7 times, and a transverse tensile temperature of 115°C. After keeping warm, a film sheet with an area increased by about 110 times is obtained, and the white oil in the film sheet is extracted using dichloromethane to form voids, and the dried microporous film is stretched again in the transverse direction at a small ratio of 1.8 times, and the transverse small tensile temperature is 133°C, and heat set at 133°C to obtain a porous polyethylene base film with a thickness of 5.2 μm and a crystallinity of 79.1%.
[0111] Example 3-11 The method described in Example 1 was followed, with the difference being that the parameters listed in Table 1 below were different from those in Example 1.
[0112] Comparative Example 1 First, the molecular weight Mw is 3.0×10 5Select the second polyethylene of the above blended with white oil, where the solid content of polyethylene is 25%, heat melt in an extruder, then cast at a lower temperature, and cool to form, to obtain a 2mm cast film sheet, and then perform longitudinal and transverse tension on the cast film sheet, with a longitudinal tension ratio of 11.2 times, a longitudinal tension temperature of 110°C, a transverse tension ratio of 10.7 times, and a transverse tension temperature of 115°C. After keeping warm, obtain a film sheet whose area is increased by 120 times, and use dichloromethane to extract the white oil in the film sheet to form voids, and after drying, the microporous film is again subjected to transverse tension at a small ratio of 2 times, and the transverse tension temperature is 133°C, and heat fixing is performed at 133°C, to obtain a porous polyethylene base film with a thickness of 5.2 μm.
[0113] Comparative Example 2 First, the molecular weight Mw is 1.0×10 5 Select the second polyethylene of the above blended with white oil, where the solid content of polyethylene is 25%, heat melt in an extruder, then cast at a lower temperature, and cool to form, to obtain a 2mm cast film sheet, and then perform longitudinal and transverse tension on the cast film sheet, with a longitudinal tension ratio of 11.2 times, a longitudinal tension temperature of 110°C, a transverse tension ratio of 10.7 times, and a transverse tension temperature of 115°C. After keeping warm, obtain a film sheet whose area is increased by 120 times, and use dichloromethane to extract the white oil in the film sheet to form voids, and after drying, the microporous film is again subjected to transverse tension at a small ratio of 2 times, and the transverse tension temperature is 133°C, and heat fixing is performed at 133°C, to obtain a porous polyethylene base film with a thickness of 5.2 μm.
[0114] Comparative Example 3-7 The method described in Example 1 was followed, with the difference being that the parameters listed in Table 1 below were different from those in Example 1.
[0115] [Table 1] [Table 1-1] [Table 1-2]
[0116] Polyethylene-based film related parameter testing 1. Puncture strength test: Cut the separator sample with a blade, and the length and width of the sample should be greater than 64mm. After checking that the Gotech tensile machine is clean, install the puncture tool, place the separator in the center of the tool, and cover it with the top cover. On the computer operation panel of the Gotech tensile machine, set the test to "separator compression" sequentially, the speed is 50mm / min, click "start", perform the puncture test sequentially, and save the force-displacement curve. Each group is tested in parallel at least three times, and when the repeatability of the three force-displacement curves is relatively good, the next group is tested. The test results are shown in Table 2 below.
[0117] 2. Tensile strength / elongation test: Spline punching: (1) Prepare a 20mm*100mm blade and wrinkle tape; (2) punch splines along the longitudinal or transverse direction according to the test requirements; each group can be punched 10 pieces; then put them into a clean sample bag according to the group and mark the group. Turn on the Gotech tensile machine, set the separator tension, speed 50mm / min, starting fixture interval 40mm, etc. in sequence, place the spline to be measured in the middle of the fixture, and clamp the upper and lower ends with the fixture respectively. Click the computer desktop tension operation screen, clear the force, displacement, etc. to zero, then click "start", perform the test, record the tensile curve after the test is completed, each group measures at least three splines, and if the repeatability of the three force-displacement curves is relatively good, perform the next group of tests. The test results are as shown in Table 2 below.
[0118] 3. Thermal shrinkage test: A 100mm*50mm blade was taken, and the separator was punched into a 100mm*50mm sample by a press. The punched 100mm*50mm separator was marked with a number in the lower right corner with a marker and measured before firing in two dimensions, and the firing temperature and time were set. After the oven reached the set temperature, the separator was placed in the oven together with the steel disk to be fired, and after the specified firing time was reached, it was taken out and left at room temperature for 10 minutes. The horizontal and vertical sizes of the separators with the same number were measured after firing, and the horizontal size was recorded as X2 and the vertical size was recorded as Y2. The vertical thermal shrinkage rate = (100-Y2) / 100*100%, the horizontal thermal shrinkage rate = (50-X2) / 50*100%, and if the shrinkage of the sample edge is uneven, it was taken from the maximum position of shrinkage. The test results are shown in Table 2 below.
[0119] 4, Air permeability test: Cut the separator sample, the sample size should be greater than 40*40mm. Turn on the power switch of the digital timer, and press the "ENTER" button on the dashboard to enter the selection screen. First loosen the bottom cock, then lift the slide barrel of the air permeability tester and hang it on the knock pin. Note: During lifting, do it slowly, prevent oil from overflowing. Place the sample on the sample test platform, the sample must cover the entire sample area, tighten the knob, select the measurement area (generally 100cc, in special cases, according to actual requirements), place the punched small film sheet on the sample test platform, ensure that the film can cover the test platform. First press the Reset key, then release the slide cylinder to start the test. After the measurement is completed, slowly loosen the cock until the slide cylinder descends to the lowest position. Take out the sample, slowly pull up the slide cylinder, and prepare for the next measurement. Note: During lifting, do it slowly, prevent oil from overflowing. Record the data in a timely manner after the measurement is completed. The test results are shown in Table 2 below.
[0120] 5. Measuring the separator thickness: Clean the measuring platform and measuring head. The measuring platform and measuring head must be kept clean. Note: When cleaning, take a small amount of alcohol with a dust-free cloth, gently wipe the bottom of the measuring head five times repeatedly, and wipe the measuring platform three times. Check whether the sample to be measured has any appearance defects such as damage, foreign matter, or paint removal (after coating). If there are any, resample. Press the "▼" key to make the measuring head tightly contact with the test platform, and press the "zero" key to clear the thickness gauge to zero. Press the "▲" key to lift the measuring head, lift the sample and place it on the test platform, hold the separator in the measuring position flat on the test platform, and align the measuring position with the measuring head. Press the "▼" button until the measuring head comes to a standstill. If the data remains stable, the data was recorded in the table. The test results are as shown in Table 2 below.
[0121] 6. Porosity test: The cut separator sample was punched with a 100mm*50mm blade to produce a rectangular sample. The length L and width W of the rectangular sample were measured. Then, the thickness was measured with a 0.1um micrometer, and the thickness values were measured at a total of five points, four points on the edge and one point in the middle (as shown below), and the average value of the five thickness points was taken as the final thickness, which was marked as T. The weighed rectangular sample was weighed with an analytical balance with an accuracy of 0.0001g, which was marked as M1. Using the measured length L, width W, thickness T, and the material density ρ of the separator, the theoretical weight of the separator was calculated, which was marked as M2: M2=L*W*T*ρ. Porosity=(1-M1 / M2)*100%.
[0122] 7. Surface density test: The cut separator sample was punched with a 100mm*50mm blade to produce a rectangular sample. The length L and width W of the rectangular sample were measured, and the weight of this sheet separator was measured and recorded as M, where surface density = M / (L*W). The test results are shown in Table 2-4 below.
[0123] [Table 2]: Test results of relevant parameters of polyethylene-based film [Table 2]
[0124] [Table 3]: Test results of relevant parameters of polyethylene-based film [Table 3]
[0125] [Table 4]: Test results of relevant parameters of polyethylene base film: [Table 4]
[0126] Using the porous polyethylene base films of Examples 1-18 and Comparative Examples 1-7, lithium ion batteries are manufactured according to the following general manufacturing method.
[0127] Lithium-ion battery manufacturing (1) The produced porous polyethylene base film was slit, and the surface of the porous polyethylene base film was coated with ceramic, and then polyvinylidene fluoride (PVDF) was sprayed on to obtain a separator.
[0128] (2) Manufacturing of positive electrodes The positive electrode active material NCM811, the conductive agent Super P, and the adhesive polyvinylidene fluoride (PVDF) were mixed in a mass ratio of positive electrode active material:Super P:PVDF=8:1:1, added to the solvent N-methylpyrrolidone (NMP), and uniformly stirred under the action of a vacuum stirrer to obtain a positive electrode slurry, in which the solid content in the positive electrode slurry is 50wt%. The positive electrode slurry was uniformly coated on a positive electrode current collector aluminum foil and dried at 85°C, then cold pressed, trimmed, cut, stripped, and finally dried under vacuum at 85°C for 4h to obtain a positive electrode plate.
[0129] (3) Manufacturing of negative electrodes The negative electrode active material graphite, conductive agent Super P, thickener sodium carboxymethylcellulose (CMC), adhesive styrene butadiene rubber emulsion (SBR) are mixed in a mass ratio of graphite:Super P:CMC:SBR=80:15:3:2, added to solvent deionized water, and uniformly stirred under the action of a vacuum stirrer to obtain a negative electrode slurry, in which the solid content in the negative electrode slurry is 30wt%. The negative electrode slurry is uniformly coated on a negative electrode current collector copper foil and dried at 85℃, then cold pressed, trimmed, cut, stripped, and finally dried under vacuum conditions at 120℃ for 12h to obtain a negative electrode plate.
[0130] (4) The positive electrode plate from step (2), the separator from step (1), and the negative electrode plate from step (3) are stacked in order, and the separator is placed between the positive and negative electrodes to play the role of isolation. Then, the stacked cells are wound into a rectangular bare cell, the tabs are welded, and the bare cell is put into a packaging foil aluminum plastic film. Then, the bare cell is baked at 80°C to remove water, and then the electrolyte is injected and sealed. Then, the stacked cells are left to stand, hot pressed and cold pressed, chemically formed (charged at a constant current of 0.02C to 3.3V, then charged at a constant current of 0.1C to 3.6V), shaping, capacity test, and other processes are carried out to obtain a finished pouch lithium ion battery, which has a thickness of 4.0mm, a width of 60mm, and a length of 140mm.
[0131] Battery performance testing 1. Battery DC internal resistance test At a certain temperature, the lithium-ion battery is charged and discharged at a high current for a short time (10s), and the DCR value can be obtained by calculating the ratio of the voltage difference and current before and after charging and discharging. The test conditions and test results are shown in Table 5 below.
[0132] 2. Short circuit rate test After winding, the bare cell is shaped and hot pressed, and a short circuit rate test is performed on the bare cell using a HIOKI INSULATION TESTER while the bare cell is under pressure. If the short circuit rate is lower than 2MΩ, the cell is determined to be defective. The test sample amount is 100ea battery cores, and the failure rate = number of failures / 100*100%, and the test results are shown in Table 5 below.
[0133] 3. Battery core hot box test The single battery core was placed in the temperature box and clamped with a large aluminum fixture, and the temperature box was heated at 1°C / min until the battery core expired, and the battery core expiration temperature was recorded. During the test, the battery core voltage, the voltage from the positive electrode to the top cover, the voltage from the negative electrode to the top cover, the positive electrode, the negative electrode, the center of the main surface, the explosion-proof port, the bottom temperature, the exhaust port position temperature, the front temperature of the sample table, and the rear temperature of the sample table were monitored. The oven temperature at the time of the battery core expiration after the test was recorded. The test results are shown in Table 5 below.
[0134] 4. Battery core thermal diffusion test The three battery cores were assembled into a module, and the battery core voltage, the voltage from the positive electrode to the top cover, and the voltage from the negative electrode to the top cover were monitored; the positive electrode, the negative electrode, the large surface center, the explosion-proof port, the bottom temperature, the exhaust port position temperature, the front temperature of the sample, and the rear temperature of the sample were monitored; the first battery core was heated to failure using a heating plate, and the failure time T1 of the first battery core was recorded; the failure of the second battery core was triggered after the first battery core went into thermal runaway, and the failure time T2 of the second battery core was recorded, and so on, and the failure time T3 of the third battery core was recorded. The test results are shown in Table 5 below.
[0135] [Table 5]: Battery performance test results [Table 5-1] [Table 5-2]
[0136] By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that Comparative Examples 1 and 2 use only one molecular weight polyethylene, and the polyethylene base film produced has low puncture strength and high heat shrinkage, and the lithium ion batteries produced with the polyethylene base films of Comparative Examples 1 and 2 have high DCR values and short circuit rates, low hot box test temperatures, and a short time required for the adjacent second battery core to thermally fail. The polyethylene base film produced in Example 1 has high puncture strength and low heat shrinkage, and the lithium ion batteries produced with the polyethylene base film of Example 1 have low DCR values and short circuit rates, high hot box test temperatures, and a long time required for the adjacent second battery core to thermally fail. Therefore, the polyethylene base film of the present application can be used as a separator for a secondary battery to improve safety performance.
[0137] As can be seen by comparing Example 1 and Comparative Example 3, the puncture strength of the polyethylene base film prepared in Comparative Example 3 is only 318gf. The lithium ion battery prepared using the polyethylene base film of Comparative Example 3 has a high DCR value and a high short circuit rate, a low hot box test temperature, and a short time required for the adjacent second battery core to thermally fail, and has poor safety performance, which is unfavorable for scale-up production.
[0138] As can be seen by comparing Example 1 and Comparative Example 4, the puncture strength of the polyethylene base film prepared in Comparative Example 4 is only 288gf. The lithium ion battery prepared using the polyethylene base film of Comparative Example 4 has a high DCR value and a high short circuit rate, a low hot box test temperature, and a short time required for the adjacent second battery core to thermally fail, and has poor safety performance, which is unfavorable for scale-up production.
[0139] As can be seen by comparing Example 1 with Comparative Examples 5-6, if the occupancy rate of polyethylene to white oil is too low, the amount of dichloromethane consumed in the extraction step increases, which is unfavorable to cost control; if the occupancy rate of polyethylene to white oil is too high, it will cause inconsistency in extrusion pressure, which is prone to cause uneven thickness on the film surface, which is unfavorable to separator quality control, and therefore the short circuit rate of the manufactured lithium ion battery will be high, which is unfavorable to scale-up production.
[0140] As can be seen by comparing Example 1 and Comparative Example 7, the puncture strength and elongation rate in Comparative Example 7 are both significantly reduced, which results in a high short-circuit rate of the manufactured lithium ion battery, which is disadvantageous for scale-up production.
[0141] The above are merely comparatively excellent specific embodiments of the present invention, and the scope of protection of the present invention is not limited thereto, and any changes or replacements that a person skilled in the art can easily think of within the technical scope of the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be in accordance with the scope of protection of the claims.
Claims
1. A polyolefin base film, comprising polyolefins having different weight average molecular weights, a thickness of the polyolefin base film of ≦6 μm, and a longitudinal shrinkage rate of the polyolefin base film of ≦2% and a transverse shrinkage rate of ≦1% at 115° C. / 1 h.
2. The thickness of the polyolefin base film is 0.5 to 6 μm, The puncture strength of the polyolefin base film is ≧380 gf, or the puncture strength of the polyolefin base film is 380 to 1000 gf, or the puncture strength of the polyolefin base film is 400 to 600 gf, The polyolefin base film according to claim 1, characterized in that the polyolefin base film has a longitudinal shrinkage rate of 0% to 1.8% and a transverse shrinkage rate of 0% to 0.8% at 115°C / 1h.
3. The polyolefin comprises a first polyethylene and a second polyethylene, The weight average molecular weight of the first polyethylene is 800,000 or more, or the weight average molecular weight of the first polyethylene is 800,000 to 3,000,000; The polyolefin base film according to claim 1, characterized in that the weight average molecular weight of the second polyethylene is ≦600,000, or the weight average molecular weight of the second polyethylene is 300,000 to 600,000.
4. The polyolefin base film according to claim 3, characterized in that the mass ratio of the first polyethylene to the second polyethylene is 3:7 to 9.9:0.
1.
5. 10. The polyolefin-based film of claim 1, wherein the polyolefin comprises one or two of polypropylene and polyethylene.
6. The polyolefin base film has a longitudinal tensile strength of ≧3800 kgf / cm 2 and the transverse tensile strength of the polyolefin base film is ≧3000 kgf / cm 2 2. The polyolefin base film according to claim 1 ,
7. The polyolefin base film is (1) The porosity of the polyolefin base film is 25 to 40%; (2) The polyolefin base film has an air permeability of 100 to 160 s / 100 cc; (3) The surface density of the polyolefin base film is 2.8 to 3.6 g / m 2 10. The polyolefin-based film of claim 1, characterized in that it has one or more of the following characteristics:
8. The polyolefin base film according to claim 1, characterized in that the polyolefin base film has a crystallinity of ≧75%, or the crystallinity of the polyolefin base film is 75-85%.
9. A method for producing a polyolefin base film, comprising the steps of: A method for producing a film sheet from a mixture of polyolefins having different weight average molecular weights and a pore-forming agent, wherein the proportion of the total weight of the polyolefin in the mixture is 15 to 35 wt %; The film sheet is biaxially stretched, and the longitudinal stretching ratio is 5 to 50 times and the transverse stretching ratio is 5 to 50 times, or the longitudinal stretching ratio is 5 to 20 times and the transverse stretching ratio is 5 to 20 times; removing the pore-forming agent to form voids; and subjecting the film sheet to tensile fixing and heat fixing to obtain a polyolefin base film.
10. The method according to claim 9, wherein the proportion of the polyolefin in the mixture is 20 to 30 wt %, the longitudinal tensile magnification is 10 to 20 times, and the transverse tensile magnification is 10 to 20 times.
11. The method according to claim 9, characterized in that the biaxial stretching makes the polyolefin base film have a crystallinity of ≧75%, or the biaxial stretching makes the polyolefin base film have a crystallinity of 75-85%.
12. The polyolefin comprises a first polyethylene and a second polyethylene, The weight average molecular weight of the first polyethylene is 800,000 or more, or the weight average molecular weight of the first polyethylene is 800,000 to 3,000,000; 10. The method according to claim 9, wherein the weight average molecular weight of the second polyethylene is ≦600,000, or the weight average molecular weight of the second polyethylene is 300,000 to 600,000.
13. The method according to claim 12, wherein a mass ratio of the first polyethylene to the second polyethylene is from 3:7 to 9.9:0.
1.
14. 10. The method of claim 9, wherein the pore-forming agent comprises one or more of white oil, liquid paraffin, mineral oil, soybean oil, phthalate ester, and aromatic ether.
15. A separator comprising the polyolefin-based film of claim 1.
16. A secondary battery comprising the separator according to claim 15.
17. A power consuming device comprising the secondary battery according to claim 16.
Citation Information
Patent Citations
Ultrathin high-strength modified lithium ion battery diaphragm and preparation method thereof
CN112332023A
Battery diaphragm casting piece, manufacturing method thereof, battery diaphragm and manufacturing method thereof
CN113809469A
Polyolefin minute porous film and method of its manufacture
JP2003105122A
Polyolefin microporous film and battery separator
JP2022048093A
Polyolefin microporous membrane, separator for cell, and cell
WO2015194504A1